1992
DOI: 10.1128/aac.36.12.2736
|View full text |Cite
|
Sign up to set email alerts
|

Cure of murine Trypanosoma brucei rhodesiense infections with an S-adenosylmethionine decarboxylase inhibitor

Abstract: The compound 5'-{[(Z)-4-amino-2-butenyl]methylamino}-5'-deoxyadenosine (MDL73811), a potent inhibitor of S-adenosylmethionine decarboxylase, was effective in mice against six of eight clinical isolates of 7rypano-soma brucei rhodesiense, the causative agent of East African sleeping sickness. In combination with the ornithine decarboxylase inhibitor DL-e-dfloromethylornithine (DFMO; Ornidyl), MDL73811 acted synergistically to cure seven of eight infections. MDL73811 was effective when given singly at 50 to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
68
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 19 publications
2
68
0
Order By: Relevance
“…Gene knockout or RNA interference (RNAi) studies in T. brucei have shown that the polyamine and trypanothione biosynthetic enzymes are required for parasite growth (1,19,23,24,35,40). In addition to DFMO, inhibitors of AdoMetDC have also been reported to have antitrypanosomal activity (3,5,7), further demonstrating that polyamine metabolism is of clear medical and pharmacological importance in these parasites. DFMO treatment depletes the cells of putrescine and trypanothione, while leading to a partial depletion of spermidine (11).…”
mentioning
confidence: 99%
“…Gene knockout or RNA interference (RNAi) studies in T. brucei have shown that the polyamine and trypanothione biosynthetic enzymes are required for parasite growth (1,19,23,24,35,40). In addition to DFMO, inhibitors of AdoMetDC have also been reported to have antitrypanosomal activity (3,5,7), further demonstrating that polyamine metabolism is of clear medical and pharmacological importance in these parasites. DFMO treatment depletes the cells of putrescine and trypanothione, while leading to a partial depletion of spermidine (11).…”
mentioning
confidence: 99%
“…Knockout of the AdoMetDC gene in the trypanosomatid Leishmania donovani led to spermidine auxotropy (11). The suicide inhibitor of AdoMetDC, MDL73811, has demonstrated efficacy in animal models of both T. brucei (12) and a related parasite Trypanosoma cruzi (13), which is the causative agent of Chagas disease. Thus, AdoMetDC is considered a promising, but as yet unexploited target for the development of new anti-trypanosomal drugs.…”
mentioning
confidence: 99%
“…This drug is also effective at killing other genera of protozoan parasites in vitro (1,9,27,49), including Leishmania promastigotes (35,37,41,49,55), and markedly ameliorates but does not eliminate short-term L. donovani infections in mice (30,37,45) and hamsters (42). In addition, inhibitors of a second enzyme in the polyamine pathway, Sadenosylmethionine decarboxylase (ADOMETDC), the enzyme that produces the decarboxylated S-adenosylmethionine substrate for the spermidine synthase (SPDSYN) reaction, are also effectual antitrypanosomal agents (2,3,6,8,9,16,18,58).…”
mentioning
confidence: 99%